Do portable nursing stations within bays of hospital wards reduce the rate of inpatient falls? An interrupted time-series analysis. (16th July 2018) - Ali, U M; Judge, A; Foster, C; Brooke, A; James, K; Marriott, T; Lamb, S E
Abstract: Background: falls can negatively affect patients, resulting in loss of independence and functional decline and have substantial healthcare costs. Hospitals are a high-risk falls environment and regularly introduce, but seldom evaluate, policies to reduce inpatient falls. This study evaluated whether introducing portable nursing stations in ward bays to maximise nurse–patient contact time reduced inpatient falls. Methods: inpatient falls data from local hospital incident reporting software (Datix) were collected monthly (April 2014–December 2017) from 17 wards in Stoke Mandeville and Wycombe General Hospitals, the UK. Portable nursing stations were introduced in bays on these wards from April 2016. We used a natural experimental study design and interrupted time series analysis to evaluate changes in fall rates, measured by the monthly rate of falls per 1000 occupied bed days (OBDs). Results: the wards reported 2875 falls (April 2014–December 2017). The fallers' mean age was 78 (SD = 13) and 58% (1624/2817) were men. Most falls, 99.41% (2858/2875), resulted in none, low or moderate harm, 0.45% (13/2875) in severe harm and 0.14% (4/2875) in death. The monthly falls rate increased by 0.119 per 1000 OBDs (95% CI: 0.045, 0.194; P = 0.002) before April 2016, then decreased by 0.222 per 1000 OBDs (95% CI: −0.350, −0.093; P = 0.001) until December 2017. At 12 months post-intervention, the absolute difference between the estimated post-intervention trend and pre-intervention projected estimate was 2.84 falls per 1000 OBDs, a relative reduction of 26.71%. Conclusion: portable nursing stations were associated with lower monthly falls rates and could reduce inpatient falls across the NHS.